Anti-CD20 therapies and pregnancy in neuroimmunologic disorders: A cohort study from Germany. Issue 1 (January 2021) - Kümpfel, Tania; Thiel, Sandra; Meinl, Ingrid; Ciplea, Andrea I.; Bayas, Antonios; Hoffmann, Frank; Hofstadt-van Oy, Ulrich; Hoshi, Muna; Kluge, Jakob; Ringelstein, Marius; Aktas, Orhan; Stoppe, Muriel; et al.
Abstract : Objective: To report pregnancy outcomes and disease activity (DA) in women with MS, neuromyelitis optica spectrum disorders (NMOSDs), and other neuroimmunologic diseases (ONID) after treatment with rituximab (RTX)/ocrelizumab (OCR) 12 months before or during pregnancy. Methods: Data were collected in the German MS and pregnancy registry and centers from the Neuromyelitis Optica Study Group. Sixty-eight known outcomes of 88 pregnancies from 81 women (64 MS, 10 NMOSD, and 7 ONID) were included and stratified in 3 exposure groups: >6M-group = RTX/OCR >6 but ⩽12 months before the last menstrual period (LMP) (n = 8); <6M group = RTX/OCR <6 months before the LMP (n = 47); preg group = RTX/OCR after the LMP (n = 13). Results: Pregnancy outcomes were similar between groups, but significantly more preterm births (9.8% vs 45%) occurred after exposure during pregnancy. Overall, 2 major congenital abnormalities (3.3%), both in the preg group, were observed. Three women had severe infections during pregnancy. All women with MS (35) and 12/13 women with NMOSD, RTX/OCR exposure before the LMP and known pregnancy outcomes after gestational week 22 were relapse free during pregnancy. Five of 29 (17.2%) women with relapsing-remitting MS (RRMS) and 1 of 12 (8.3%) with NMOSD and at least 6 months postpartum follow-up experienced a relapse postpartum. Duration of RTX/OCR and early retreatment but not detection of B-cells were possible predictors for postpartum relapses in patients with RRMS/NMOSD. Conclusions: Although RTX/OCR might be an interesting option for women with RRMS/NMOSD who plan to become pregnant to control DA, more data on pregnancy outcomes and rare risks are needed.